The Pathological Mechanisms of Obesity-Related Glomerulopathy: A review article - Kasim, Ali A.; Ataimish, Ahmed H. (Iraqi Journal of Pharmaceutical Sciences, 2021)
The rising prevalence of obesity-related glomerulopathy (ORG) occurs in accordance with the rising prevalence of obesity worldwide. Clinically ORG is manifested by slowly progressing microalbuminuria that may develop to clinically evident proteinuria. Pathological characteristics of ORG include glomerular hypertrophy in the presence or absence of focal segmental glomerulosclerosis (FSGS). ORG can develop into clinically overt chronic renal insufficiency or even end-stage kidney disease. This article reviews the most important mechanisms for the development of ORG; that are abnormal renal hemodynamics, stimulation of renin-angiotensin-aldosterone system (RAAS), impairment of insulin sensetivity, ectopic lipid deposition, adipose tissue cytokine disorder and local renal micro-inflammation.